(untitled) (Research, Society and Development, 2022)
Objectives: To identify and evaluate innovation strategies with urgent and emergency applications in Brazilian literature. Methods: This was a systematic review of the literature. The PRISMA statement was followed at all stages of this study. The selection of articles was carried out in the databases PubMed / Medline, Web of Science, VHL (Medline, Lilacs, IBECS, BDENF) and SciELO library without a specific date. The PICOS strategy: “patient, intervention, comparison, results and study design” was followed and the search carried out resulted in the selection of ten articles. Results: The main findings were theses, articles with themes extracted from master’s theses and integrative literature reviews, in which new instruments and applications for care practice were validated, which were evaluated by the nursing team. It is worth mentioning that care, in all its dimensions, requires continuous updating, allowing a range of possibilities to expand knowledge in the area. Conclusion: The study allowed us to understand that the insertion of technology, although little reported in the literature, causes a mixture of feelings in the daily care, since it allows autonomy and practicality of professionals. It is worth mentioning that care, in all its dimensions, requires continuous updating, allowing a range of possibilities to expand knowledge in the area.